Social Identity Negotiation in Online Communication: Understanding the Formation of Violent Normalization as Means to Deal with Violent Crimes in Online Facebook Group ‘Info Cegatan Jogja’ - Muhammad Affan Asyraf; Megawati Sukarno Putri; Aulia Devi Qiara; Ardifya Nandhia Kirana; Muhammad Naufal Dzakki (Department of Communications, Universitas Islam Indonesia, 2021)
In the last decade, street violence in the Special Region of Yogyakarta (DIY) has increased immensely. Whether intentional or organized, violence has become news, increasingly appearing on various media and social platforms. This phenomenon contradicts the predicate of Yogyakarta as a city of students and a city of culture. Through such background, this study encourages investigating the socio-cultural contexts of such increasing violence in a city, promoting its branding as a non-violence city. This study analyses one of the largest online social platforms in Yogyakarta, called ‘Info Cegatan Jogja’ (ICJ). Applying an ethnographic approach, quantitative and qualitative data were collected and analyzed using the sentiment analysis method. The study finds that the high rate of violence is not solely the result of street violence itself, but is also supported by the act of justifying violence with the general idea that the accurate way to deal with violence is through violence. In other words, society begins to assume that if it is treated as a curative measure, then violence is accepted as something to be normalized. Keywords: Violence, Info Cegatan Jogja, social media, negotiation, violent normalization.